Mindful parenting and behavioural problems in preschool children - Maglica, Toni (Array, 2020)
The aim of this research was to find out if mindful parenting contributes to internalised and externalised problems in preschool children. A total of 168 mothers, fathers and preschool teachers took part in the research, which assesses the extent of internalised and externalised problems in 76 preschool children. Additionally, both parents completed the Mindfulness in Parenting Questionnaire. Results showed that internalised and externalised problems were significantly correlated, with externalised problems being more prominent in boys. Mothers and fathers differed only in one aspect of mindful parenting, empathic understanding for the child, which was higher in mothers. When analysing differences in mindful parenting of boys/girls, the results showed that fathers of boys have higher parental awareness than fathers of girls, while there were no other significant differences. Mindful parenting did not prove significant in predicting internalised problems of preschool children. In contrast, the results showed that 30% of externalised problems in children can be explained by the child’s gender and by mindful parenting from both parents. These findings point to some differences between mothers and fathers contributing to externalised problems. Specifically, the father’s focusing attention on the child with acceptance and the mother’s self-efficacy were related to lower externalising problems, while the father’s empathic understanding of the child and mother’s non-reactivity were related to more externalising problems in children. The results are discussed in the context of existing knowledge about implicit parenting and child development outcomes.